PAG electrophoregrams of six Finnish potato cultivars - Tuula Sontag; Hannu Salovaara; Osmo Ulvinen (Agricultural and Food Science, 1985)
The polyacrylamide gel electrophoretic (PAGE) patterns of soluble proteins and esterases of six Finnish potato cultivars (Jaakko, Pito, Hankkijan Timo, Hankkijan Tuomas, Hankkijan Tanu and Puikula) were determined. All cultivars are commonly grown in Finland. The PAGE procedure used yielded highly reproducible protein separation and good resolution. Samples studied had specific soluble protein and esterase PAGE patterns, indicating that electrophoregrams can be used for identifying Finnish potato cultivars. Only two cultivars, Hankkijan Tanu and Hankkijan Tuomas, which are close relatives, possessed very similar PAGE patterns. The electrophoretic pattern of Puikula was very similar to that of the Swedish cultivar Mandel when compared with the reference presented in the literature.Therefore a hypothesis is presented suggesting that these two local cultivars would be representatives of the same cultivar.